Determination of quality in stored pear fruits by chemical analysis and sensorial judgement - Takácsné Hájos, M.; Nyéki, J.; Illés, A.; Sipos, Gy.; Szabó, Z. (International Journal of Horticultural Science, 2016)
Aim of this research/project to determine the external and internal preferences of pear using descriptive sensory analysis, consumer preference. The research was performed on local consumers. Destructive measurements included fi rmness by puncture tests, soluble solids content (SSC), titrated acidity (TA). While there is a general positive trend for increasing preference with fi rmness, some consumers will prefer softer apples, and some will dislike the fi rmest pear. Sensorial judgement is able to classify the attractiveness, preference of properties specifi c for pear. Tests were performed by 13 persons on 4 pear varieties (Bosc kobak, Conference, Packham’s Triumph, Dessertnaia) checking 11 sensorial properties on a scale of 1 to 100 points. Relations of measurements and judgements were processed by correlation analysis. For analysis, the objects were furnished in 2011 from different growing sites (Csenger, Mérk and Nagykanizsa), taking from the store (in January) immediately. Among those the best notes were given to Bosc kobak and Conference coming from Mérk and to Packham’s Triumph grown at Nagykanizsa. It was stated that the success of sensorial judgement depends on the state of maturity, which is diffi cult to guarantee to be synchronous among samples of different varieties. Mature fruits are more praised as a sample of Bosc kobak taken from a chain of department store proved to be of balanced composition regarding its sugar/acid ratio (0.12) and the optimal fi rmness (5.75 N/cm2). Results of the correlation analysis suggest that the thickness of the skin is a decisive component of preference (r= 0.857), the typical pear flavour (r= 0.948), the taste as sweetness and acidity (r= 0.930 and r= 0.813). At the same time, no valuable relation could be detected between the data raised in the laboratory and the preference expressed by the sensorial tests, which should signalise that the opinion of consumers does not depend on any individual parameter obtained in the laboratory (sugar- or acid content, fi rmness) but rather on the complexity of several decisive components together (sweetness, acidity, fl avour, skin, etc.). The consumers’ preference cannot be measured objectively without the aid of adequate expertise and a prosperous surrounding, samples of optimal maturity and a thoughtfully edited judging form.